Linear dunes on Titan and earth: Initial remote sensing comparisons - Radebaugh, J.; Lorenz, R.; Farr, T.; Paillou, P.; Savage, C.; Spencer, Christopher (Elsevier BV, 2010)
Thousands of dunes found in Cassini Radar images of the equatorial regions of Titan, a moon around Saturn, are similar in size and morphology to linear dunes on Earth. We present remote sensing images of terrestrial analogues to the dunes on Titan obtained by Landsat and radar, both at considerably higher resolution than are available at Titan, that provide information about dune landforms and processes. Dunes are generally dark to radar, indicating smooth surfaces and signal absorbing materials, but at certain incidence angles, dune surfaces can reflect the radar signal and lead to a bright return. Linear dunes on Titan and Earth diverge around topographic obstacles, creating teardrop patterns that indicate mean direction of wind flow and sand transport. When sand supply or wind conditions change in linear dune fields, such as behind an obstacle or near the margin of the dune field, dunes disappear, change size and spacing, or change dune type. These comparisons of features on Titan and Earth provide a better understanding of the global, sand-transporting wind directions, sand properties and supply, and the nature of the underlying substrate, on Titan.